Penerapan Teknologi Tepat Guna Bagi Kelompok Usaha Kecil Jamu Tradisional di Kecamatan Sampang Madura - Siti Mujanah; Achmad Maqsudi; Harjo Seputro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
Abstract.Â The market opportunities of herb medicine in Indonesia is quite widespread both for domestic needs and for export. Domestic demand for herb medicine was increased each year. This mean that the opportunities to develop the household or small scale herb industries in Indonesia are needed, one of the most popular place of herb medicine in Indonesia is Madura Island, especially in this present the local government of Sampang District concern to develop the Central of Herb Medicine in Jl Pahlawan, and they called â€œHerb Medicine Putri Pahlawan Cluster. According to our survey we found that they have several problems in management such as marketing, financial and technology, therefore we over the management training to the members of cluster and make a machine or applied technology for producing in the bigger volume ofproduction.Â Keywords: Applied Technologi, Marketing Management and Finacial management